DEVELOPMENT AND INTRODUCTION OF THE CULTIVATOR FOR FOR THE SOIL TILLAGE AT ROW-SPACINGS AND VINEYARDS LINES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of theoretical and experimental studies on finding the optimal scheme of a cultivator for tillage in vineyards, providing high-quality tillage with minimal energy (power) consumption. The basic parameters of the machine and operational elements are substantiated.